2013
DOI: 10.1038/npp.2013.336
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain-Specific CRF Overproduction During Development is Sufficient to Induce Enduring Anxiety and Startle Abnormalities in Adult Mice

Abstract: Corticotropin releasing factor (CRF) regulates physiological and behavioral responses to stress. Trauma in early life or adulthood is associated with increased CRF in the cerebrospinal fluid and heightened anxiety. Genetic variance in CRF receptors is linked to altered risk for stress disorders. Thus, both heritable differences and environmentally induced changes in CRF neurotransmission across the lifespan may modulate anxiety traits. To test the hypothesis that CRF hypersignaling is sufficient to modify anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 49 publications
5
34
0
Order By: Relevance
“…These data are consistent with our and others' previous reports showing reduced PPI and habituation following developmental or lifetime CRHOE (Dirks et al, 2002;Groenink et al, 2008;Toth et al, 2014). Pharmacological and genetic manipulation studies reported increased startle and reduced PPI following CRHR1 receptor hypersignaling, whereas CRHR2 receptor stimulation increased PPI (Risbrough et al, 2003(Risbrough et al, , 2004.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These data are consistent with our and others' previous reports showing reduced PPI and habituation following developmental or lifetime CRHOE (Dirks et al, 2002;Groenink et al, 2008;Toth et al, 2014). Pharmacological and genetic manipulation studies reported increased startle and reduced PPI following CRHR1 receptor hypersignaling, whereas CRHR2 receptor stimulation increased PPI (Risbrough et al, 2003(Risbrough et al, , 2004.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, predator stress increased avoidance of the light chamber in females regardless of CRHOE dev exposure ( Figure 1 and Table 2). CRHOE dev females also exhibited a trend for increased avoidance in non-stressed groups (duration: F stress × CRHOE (1,32) = 3.49, p = 0.071, post hoc: p = 0.098; Table 2) as described previously (Toth et al, 2014).…”
Section: Avoidance In the Light-dark Boxsupporting
confidence: 75%
See 3 more Smart Citations